Game based implementation of cognitive behavioral therapy for introspective treatment of social anxiety disorder - Nur Mahirah Mohamad Saleh,; Hafiz Mohd Sarim,; Siti Fadzilah Mat Noor, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Social anxiety disorder (SAD) is one of the most common mental health disorders in society worldwide. The prevalence rate is increasing within the population and this can affect an individual’s quality of life and economic productivity. Cognitive Behavioral Therapy is an effective psychotherapy in treating SAD. Technological interventions through serious games in the treatment of SAD are seen as one of the alternatives in solving issues related to the conventional therapy. The Social Phobia Game was developed as the primary research instrument, for the acquisition of knowledge, awareness, and for self-treatment of SAD. It is a structure-based introspective computer game prototype developed based on the proposed framework presented in this paper, which is tested in an extensive evaluation phase. The evaluation phase is conducted through an effectiveness evaluation and usability evaluation. The results of the effectiveness evaluation showed a score difference of 15% in the pre-test and post-test user responses. Meanwhile, the results of the usability evaluation gave a high mean score of over 4.00. Thus, from the results of the effectiveness and usability evaluation, the framework implemented in the serious game prototype was seen to be able to help identify, manage, and raise awareness about SAD.